Media use among children with ASD: Perspectives and concerns of parents - Larissa Pliska; Olga Kunina-Habenicht; Ute Ritterfeld (PLoS ONE, 2025)
Digital media is a significant part of daily life for both adults and children, raising concerns among parents about its impact on child development, particularly for those with autism spectrum disorder (ASD). This study explores the differing perspectives and concerns of parents with and without ASD regarding their children’s media use. A total of 117 parents of children with ASD and 58 parents of typically developing (TD) children participated in an online survey. The study employed group comparisons, correlations, and hierarchical regressions. Results show that parents of children with ASD expressed greater concern about media use compared to TD parents, especially regarding potential negative effects on health and behavior. However, these concerns did not extend to child development or intensification of ASD symptoms. Key predictors of parental concern included challenges in limiting media use, perceptions of media preference and addiction, and children’s ability to cope without media. While parents of children with ASD have notable concerns about media use, these are not excessively pronounced compared to TD parents. Many report allowing digital media as a means for self-regulation in their children. Future research should also examine positive aspects of digital media usage as potential influencing factors.